High-Sensitivity C-Reactive Protein as a Predictor of Cardiovascular Events after ST-Elevation Myocardial Infarction - Daniel Rios Pinto Ribeiro; Adriane Monserrat Ramos; Pedro Lima Vieira; Eduardo Menti; Odemir Luiz Bordin Jr.; Priscilla Azambuja Lopes de Souza; Alexandre Schaan de Quadros; Vera Lúcia Portal (Arquivos Brasileiros de Cardiologia, 2014)
Background: The association between high-sensitivity C-reactive protein and recurrent major adverse cardiovascular events (MACE) in patients with ST-elevation myocardial infarction who undergo primary percutaneous coronary intervention remains controversial. Objective: To investigate the potential association between high-sensitivity C-reactive protein and an increased risk of MACE such as death, heart failure, reinfarction, and new revascularization in patients with ST-elevation myocardial infarction treated with primary percutaneous coronary intervention. Methods: This prospective cohort study included 300 individuals aged >18 years who were diagnosed with ST-elevation myocardial infarction and underwent primary percutaneous coronary intervention at a tertiary health center. An instrument evaluating clinical variables and the Thrombolysis in Myocardial Infarction (TIMI) and Global Registry of Acute Coronary Events (GRACE) risk scores was used. High-sensitivity C-reactive protein was determined by nephelometry. The patients were followed-up during hospitalization and up to 30 days after infarction for the occurrence of MACE. Student's t, Mann-Whitney, chi-square, and logistic regression tests were used for statistical analyses. P values of ≤0.05 were considered statistically significant. Results: The mean age was 59.76 years, and 69.3% of patients were male. No statistically significant association was observed between high-sensitivity C-reactive protein and recurrent MACE (p = 0.11). However, high-sensitivity C-reactive protein was independently associated with 30-day mortality when adjusted for TIMI [odds ratio (OR), 1.27; 95% confidence interval (CI), 1.07-1.51; p = 0.005] and GRACE (OR, 1.26; 95% CI, 1.06-1.49; p = 0.007) risk scores. Conclusion: Although high-sensitivity C-reactive protein was not predictive of combined major cardiovascular events within 30 days after ST-elevation myocardial infarction in patients who underwent primary angioplasty and stent implantation, it was an independent predictor of 30-day mortality.